Mechanisms of immune tolerance to allergens: role of IL-10 and Tregs - Akdis, Cezmi A.; Akdis, Mübeccel (The Journal of clinical investigation, 2014)
During the past 20 years, major advances have been made in understanding the molecular and cellular mechanisms of allergen tolerance in humans. The demonstration of T cell tolerance, particularly that mediated by the immune-suppressive functions of IL-10, led to a major conceptual change in this area. Currently, the known essential components of allergen tolerance include the induction of allergen-specific regulatory subsets of T and B cells, the immune-suppressive function of secreted factors, such as IL-10 and TGF-β, the production of IgG4 isotype allergen-specific blocking antibodies, and decreased allergic inflammatory responses by mast cells, basophils, and eosinophils in inflamed tissues.